MINI-INVASIVE SURGICAL APPROACHES TO THE AORTO-ILIAC SEGMENT - H. Abrashev (Trakia Journal of Sciences)
Traditional open surgery of the abdominal aorta and iliac segment is a surgical intervention with a relatively high risk and well-studied perioperative mortality. Over the last decade, there has been a constantly growing trend to reduce surgical trauma in the treatment of vascular diseases. The right choice of a vascular approach is crucial for the success of every open aorto-iliac vascular reconstruction. The mini-invasive vascular approaches offer significant advantages over classic surgery and are associated with better perioperative results.